Laos: Jhai Foundation's Remote IT Village project - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Jhai Foundation´s Remote IT Village project has developed a solid-state, low-wattage computer that can be powered by a foot-crank and batteries, a high-bandwidth wireless network, to support village microenterprises.